The body by the sea - Bannalec, Jean-Luc, 1966- (Bannalec, Jean-Luc, 1966- Brittany mystery, 2023)
"In all of Commissaire Georges Dupin's time living in Brittany, there has never been a murder on his home turf, until now, in Jean-Luc Bannalec's The Body by the Sea. A town on the sea, Concarneau's nickname is Ville Bleue, or the Blue Town. With three harbors at its center, visitors can see enormous ships, sailors, fishermen, and the industry that goes alongside it. Because of its geographical location, Concarneau has shown it's perfectly positioned to protect its inhabitants from enemy attacks. For this reason and more, including his favorite restaurant, the Amiral, Commissaire Georges Dupin calls this town home. Most of his colleagues are on vacation for the Pentecost long weekend, but Dupin remains. His future in-laws are coming to visit. But what happens when an enemy attacks from within? Dupin's plans as host must change when the body of Doctor Chaboseau is discovered. Chaboseau fell to his death, pushed from his home above the Amiral. With only two new colleagues to help-no one else is answering their phone-Dupin is tasked with finding out what happened to the doctor"--